PERAN FISIOTERAPI DALAM PENCEGAHAN CEDERA HAMSTRING PADA PEMAIN FUTSAL - Marliana; Annisa, Aulia; Anavira, Sausan (Journal of Hospital Administration and Management (JHAM), 2024)
Hamstring injuries are among the most common musculoskeletal injuries experienced by futsal players due to explosive movements such as sprinting, rapid directional changes, and powerful kicks. Physiotherapy plays a crucial role in preventing hamstring injuries through strength training, stretching, and proper biomechanical techniques. This study aims to analyze the role of physiotherapy in preventing hamstring injuries in futsal players. This research employs a qualitative descriptive design using in-depth interviews and observations with futsal players undergoing preventive physiotherapy programs. The sample consists of professional and amateur futsal players with a history of hamstring injuries or at risk of experiencing them. Data were analyzed to identify the most effective physiotherapy strategies in reducing injury risk. The results indicate that physiotherapy programs incorporating eccentric hamstring exercises, dynamic stretching, pelvic stabilization techniques, and biomechanical education significantly reduce the risk of hamstring injuries in futsal players. Additionally, fatigue management and proper recovery strategies also contribute to preventing recurrent injuries. Therefore, physiotherapy should be an integral part of futsal players' training programs to enhance performance and reduce injury risks.